A comparative evaluation of the anticaries efficacy of herbal extracts (Tulsi and Black myrobalans) and sodium fluoride as mouthrinses in children: A randomized controlled trial - N Megalaa; K Thirumurugan; G Kayalvizhi; R Sajeev; E B Kayalvizhi; V Ramesh; Abhishek Vargeese (Wolters Kluwer Medknow Publications, 2018)
Background: Dental caries is a multifactorial disease in which microorganisms play an important role. Recently, herbs have been tried as mouthrinses to combat the side effects of chemical mouthrinses. The anticaries efficacy of Sodium fluoride, Tulsi leaf, and Black myrobalans fruit extracts on Streptococcus mutans (S. mutans) have been reported in the literature, but no comparative study has been done yet. Aim: This study aims to observe the change in the pH of saliva and to assess the efficacy of the herbal rinses-Tulsi and Black myrobalans on S. mutans count while comparing it with Sodium fluoride mouthrinse. Methods: Herbal ethanolic extracts of Tulsi (4%) and Black myrobalans (2.5%) were prepared as mouthrinses and compared with sodium fluoride mouthrinse (0.05%). Sixty high caries risk patients were selected and allocated randomly into three groups [n = 20], categorized as Group A-Sodium fluoride mouthrinse, Group B-Tulsi mouthrinse, and Group C-Black myrobalans mouthrinse. They were instructed to rinse their mouth with their assigned mouthrinses for 7 days. Salivary samples were collected and sent to the laboratory at baseline, 1 h postrinsing and after 7th day of rinsing for determining the salivary pH and S. mutans count. The increase in pH and reduction of S. mutans were determined. The values obtained were tabulated and statistically analyzed. Results: There was a significant increase in the salivary pH and reduction in S. mutans count after rinsing in all the three groups. Increase in salivary pH was more in the Sodium fluoride mouthrinse when compared to the experimental herbal groups (Group B and Group C). While S. mutans counts reduced more with Tulsi mouthrinse at 1 h postrinsing and after the 7th day of rinsing more reduction was seen in Black myrobalans mouthrinse group. Conclusion: The results of the study suggest that herbal mouthrinses could be tried as an adjunctive anticaries agent against dental caries causing microorganisms.